Position/force control of master–slave antagonistic joint actuated by water hydraulic artificial muscles. (13th June 2019) - Ning, Dayong; Che, Jinkai; Zhang, Zengmeng; Tian, Hao; Hou, Jiaoyi; Gong, Yongjun
Because of the high force–weight ratio of water hydraulic artificial muscle and its high compatibility with an underwater environment, the water hydraulic artificial muscle has received increasing attention due to its potential uses in marine engineering applications. The master–slave anthropopathic joint actuated by water hydraulic artificial muscles is light and small, and it has good maneuverability for underwater manipulators. However, the control methodologies for water hydraulic artificial muscle joint have not been thoroughly explored to date. This article introduces a master–slave control system of isomorphic artificial muscle joints. The water hydraulic artificial muscle joint acts as a slave joint working under the sea, and the pneumatic artificial muscle joint acts as a master joint that is operated by people. The rotation angle signal of the pneumatic artificial muscle joint is fed back as the input to regulate the rotation angle of the water hydraulic artificial muscle joint through a proportional–integral–derivative control. Meanwhile, the torque of the pneumatic artificial muscle joint is controlled by a proportional–integral–derivative controller based on the feedback of a two-force-transducer system in the water hydraulic artificial muscle joint as input. Therefore, the operator can control the movement and feel the load of the water hydraulic artificial muscle slave joint. Master–slave control experiments were performed, and the position/torque control results were analyzed using various loads and torque gains. This study contributes to the design and control of an anthropopathic underwater manipulator.